Supplementation of silicon oxide nanoparticles mitigates the damaging effects of arsenic stress on photosynthesis, antioxidant mechanism and nitrogen metabolism in Brassica juncea - Mohammad Faisal; Aynur Bilmez Ozcinar; Erdal Karadeniz; Mohammad Faizan; Haider Sultan; Abdulrahman A. Alatar (Scientific Reports)
Abstract Nanoparticles (NPs) represent one of the most promising platforms for addressing challenges in drug delivery, biosensing, and the development of advanced biotechnological tools. These innovative materials are revolutionizing modern agriculture by enabling precision farming practices that optimize resource utilization and enhance crop productivity. This study investigates the role of silicon oxide nanoparticles (SiO2 NPs, 200 ppm) in mitigating arsenic (As, 50 µM) toxicity in Brassica juncea. The results demonstrate that As stress significantly impaired morphological and physiological parameters, as well as the accumulation of key metabolites, including flavonoids, phenolics, proteins, soluble sugars, and free amino acids. However, foliar application of SiO2 NPs effectively alleviated As-induced toxicity by enhancing antioxidant enzyme activities and maintaining nutrient homeostasis. The application of SiO2 NPs also positively influenced growth parameters, net photosynthetic rate, stomatal conductance, and soluble sugar content. Notably, SiO2 NPs improved the transpiration rate by 52%, leaf nitrogen content by 33%, and phenolic content by 42%. Furthermore, there was a significant reduction in oxidative stress markers, with hydrogen peroxide and malondialdehyde levels decreasing by 41% and 39%, respectively, indicating reduced oxidative damage and lipid peroxidation. These findings underscore the promising potential of SiO2 NPs in mitigating As stress and offer valuable insights for promoting sustainable crop production under environmental stress conditions.